GLOBECOM '03. IEEE Global Telecommunications Conference (IEEE Cat. No.03CH37489)
DOI: 10.1109/glocom.2003.1259009
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive prediction based approach for congestion estimation in active queue management (APACE)

Abstract: Abstract-I. INTRODUCTION Active Queue Management (AQM) policies attempt to estimate the congestion at a node and signal the incipient congestion by dropping packet(s) before the buffer is full. The main aim of the RED [1] scheme was of providing "congestion avoidance" by dropping packets in anticipation of congestion. The performance of the RED algorithm depends significantly upon the setting of each of its parameters, which appears to be a difficult problem. In [5], Hollot et al. have studied the problem of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…As a common testbed for AQM algorithms [1,5,6] we consider a network with a dumbbell topology where each source node at one side of a bottleneck link is paired with a sink node at the other side of the bottleneck link. The bottleneck link has a capacity of 1Mbps while the other links in the network have a capacity of 3Mbps so that this simulation is identical to the APACE simulation in [6].…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a common testbed for AQM algorithms [1,5,6] we consider a network with a dumbbell topology where each source node at one side of a bottleneck link is paired with a sink node at the other side of the bottleneck link. The bottleneck link has a capacity of 1Mbps while the other links in the network have a capacity of 3Mbps so that this simulation is identical to the APACE simulation in [6].…”
Section: Simulationsmentioning
confidence: 99%
“…In particular, NLMS was used to adapt the weights on previous measurements of the queue length in order to predict the queue value at a future time. Simulation results in [6] showed that the APACE method was better able to control the instantaneous queue than RED [1], SRED [2] and AVQ [8].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, prediction method should accurately capture the traffic characteristics. Second, there are many prediction methods, including neural network [4,24], wavelet [25], adaptive filtering [4,17], time series analysis [26, 27], etc. As neural network needs a mass of training samples, it increases time and space complexity.…”
Section: Noekf Algorithmmentioning
confidence: 99%
“…Upon receiving this information, the host decreases its sending rate, so congestion can be avoided or mitigated. Current AQM algorithms can be mainly cataloged into following types: queue-size-based [3,4], traffic-rate-based [5][6][7], the combination of queue-size-based and rate-based [8], control-theory-based [9][10][11][12], etc. In fact, each AQM algorithm includes two parts: one part estimates the incipient congestion and the other part makes dropping decision based on the estimation.…”
Section: Introductionmentioning
confidence: 99%